The study of second language acquisition - Ellis, Rod (Oxford applied linguistics, 2008)
This book is an encyclopedic survey of second language acquisition research as this has developed over the last forty years. It provides sections on the description of learners' language, the role of the linguistic environment and social context, internal mechanisms, individual learner differences, and the role of instruction. It provides a balanced account by representing a variety of perspectives, including cognitive, linguistic, sociocultural, and neurolinguistic.